Implications of VEGF gene sequence variations and its expression in recurrent pregnancy loss. Issue 6 (December 2021) - Amin, Ina; Pandith, Arshad A.; Manzoor, Usma; Mir, Syed Hussain; Afroze, Dil; Koul, Aabid Mustafa; Wani, Saima; Ahmad, Aabida; Qasim, Iqbal; Rashid, Masarat; Wani, Umer M.; Anwar, Iqra; et al.
Abstract: Research question: What is the association between VEGF gene sequence variants and its mRNA expression in recurrent pregnancy loss (RPL)? Vascular endothelial growth factor (VEGF) has a prominent role in pregnancy and affects pregnancy outcome. The association of VEGF gene 1154G>A, 634G>C and 583C>T polymorphic variations with cases of RPL and full-term fertile women as controls was investigated. Design: Two hundred women with RPL and 240 women healthy controls were included. The restriction fragment length polymorphism method was used for genotyping and quantitative real-time polymerase chain reaction was used for analysis of mRNA expression. Results: In VEGF 1154G>A, significant differences were found in homozygous AA genotype between case and control participants. The variant allele A frequency was significantly more abundant in RPL cases (0.41) than controls (0.19) ( P < 0.0001). Only RPL cases with the multi-generation family history of miscarriages and those without any history showed significant differences of combined genotype GA+AA ( P < 0.0001). In VEGF 634 G>C, CC genotype and allele C showed significantly increased frequency in RPL cases compared with healthy controls ( P < 0.0001). The association between VEGF -1154 G>A SNP and VEGF-A mRNA expression levels was significant in RPL cases ( P  = 0.004). Also in VEGF-583 C>T, CT genotypes were seen significantly associated with cases ( P = 0.003). The heterozygous genotype GA was significantly ( P  = 0.03) associated with upregulation and downregulation of VEGF mRNA, whereas the homozygous variant genotype AA only leads to low expression levels of VEGF mRNA in patients with RPL. Conclusions: All the variants of VEGF play a vital role in an increased susceptibility to RPL. Also, VEGF -1154, AA genotypes are associated with its altered low mRNA expression in women with RPL and seem to affect pregnancy outcome.